A Hypomorphic Mutation in Lpin1 Induces Progressively Improving Neuropathy and Lipodystrophy in the Rat - Mul, Joram D. (American Society for Biochemistry and Molecular Biology, 2011)
The Lpin1 gene encodes the phosphatidate phosphatase (PAP1) enzyme Lipin 1, which plays a critical role in lipid metabolism. In this study we describe the identification and characterization of a rat model with a mutated Lpin1 gene (Lpin1(1Hubr)), generated by N-ethyl-N-nitrosourea mutagenesis. Lpin1(1Hubr) rats are characterized by hindlimb paralysis and mild lipodystrophy that are detectable from the second postnatal week. Sequencing of Lpin1 identified a point mutation in the 5′-end splice site of intron 18 resulting in mis-splicing, a reading frameshift, and a premature stop codon. As this mutation does not induce nonsense-mediated decay, it allows the production of a truncated Lipin 1 protein lacking PAP1 activity. Lpin1(1Hubr) rats developed hypomyelination and mild lipodystrophy rather than the pronounced demyelination and adipocyte defects characteristic of Lpin1(fld/fld) mice, which carry a null allele for Lpin1. Furthermore, biochemical, histological, and molecular analyses revealed that these lesions improve in older Lpin1(1Hubr) rats as compared with young Lpin1(1Hubr) rats and Lpin1(fld/fld) mice. We observed activation of compensatory biochemical pathways substituting for missing PAP1 activity that, in combination with a possible non-enzymatic Lipin 1 function residing outside of its PAP1 domain, may contribute to the less severe phenotypes observed in Lpin1(1Hubr) rats as compared with Lpin1(fld/fld) mice. Although we are cautious in making a direct parallel between the presented rodent model and human disease, our data may provide new insight into the pathogenicity of recently identified human LPIN1 mutations.